2015
DOI: 10.1038/srep15219
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of background music on episodic memory and autonomic responses: listening to emotionally touching music enhances facial memory capacity

Abstract: The aim of this study was to investigate how background auditory processing can affect other perceptual and cognitive processes as a function of stimulus content, style and emotional nature. Previous studies have offered contrasting evidence, and it has been recently shown that listening to music negatively affected concurrent mental processing in the elderly but not in young adults. To further investigate this matter, the effect of listening to music vs. listening to the sound of rain or silence was examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 60 publications
5
45
1
1
Order By: Relevance
“…A recent study done by Proverbio and his colleagues to find out the effect of memory on different auditory backgrounds has shown a significant effect of music on memory in which listening to emotionally touching music enhanced the facial memory capacity. [7] But no such effect on memory encoding was seen in our findings although the mean of final scores for relaxation music as well as for silence were highest but the results came out to be statistically insignificant.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…A recent study done by Proverbio and his colleagues to find out the effect of memory on different auditory backgrounds has shown a significant effect of music on memory in which listening to emotionally touching music enhanced the facial memory capacity. [7] But no such effect on memory encoding was seen in our findings although the mean of final scores for relaxation music as well as for silence were highest but the results came out to be statistically insignificant.…”
Section: Resultscontrasting
confidence: 79%
“…Available work suggests that listening to emotionally touching music enhances facial memory. [7] Various studies conducted previously on this effect of music or background noise on short term memory, reflect mixed results. It has been shown that unattended speech (speech that is not relatable to the task at hand) as well as vocal music impairs textual memory tasks, [6,8] however, Wallace and his colleagues documented and validated the use of music to enhance memory performance.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, background music changes arousal level, mood and emotional state, and alters the influence of other environmental factors on cognitive functions and emotional regulation (Koelsch, ; Moore, ; Peretz & Hébert, ; Proverbio et al, ; Trehub, ; Wilson & Brown, ). The emotional content of stimuli and events might also interact with Music and influence encoding and remembering of the episodic memories (Eschrich, Münte, & Altenmüller, ; Mitterschiffthaler, Fu, Dalton, Andrew, & Williams, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining the effects of music on human behavior and cognitive functions have indicated that music might have positive, negative or no effect on cognitive functions (Koelsch, ; Moore, ; Proverbio et al, ; Wilson & Brown, ). These variabilities in the outcome of exposure to music might be related to the multifaceted effects of music on various brain functions.…”
Section: Introductionmentioning
confidence: 99%
“…Dentro de las propuestas de percepción musical que se utilizan de modo simultáneo a la adquisición de información, el uso de la música de fondo presenta algunos antecedentes, aunque controversiales. Los estudios que reportan beneficios de la escucha de música de fondo sobre la memoria justifican el efecto teniendo en cuenta la influencia positiva que genera la música sobre el nivel de activación (arousal) y el estado de ánimo (Proverbio, y otros, 2015). Por ejemplo, un estudio realizado por Ferreri, Aucouturier, Muthalib, Bigand, y Bugaiska (2013) solicitó a un grupo de adultos jóvenes que aprendieran una lista de palabras en un contexto con música de fondo o silencio, midiendo por una parte, el rendimiento de la memoria a través de una tarea de reconocimiento, y por otra parte, monitoreando la actividad de la corteza prefrontal dorsolateral durante la fase de codificación.…”
Section: Resultsunclassified